ON A HILBERT PROBLEM IN THE HALF-PLANE IN THE CLASS OF CONTINUOUS FUNCTIONS - Aghekyan, S.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
We study the Hilbert boundary value problem in the half-plane, when the boundary function is continuous on the real axis. It was proved that this problem is Noetherian and the solutions of the corresponding homogeneous problem are determined in explicit form.